Uridine adenosine tetraphosphate induces contraction and relaxation in rat aorta - Linder, A. Elizabeth; Tumbri, Michelle; Linder, Felipe F.P.; Webb, R. Clinton; Leite, Romulo (Vascular pharmacology, 2008)
Uridine adenosine tetraphosphate (Up 4A) has been recently reported as an endothelium-derived vasoconstrictor and plasma levels of this dinucleotide are increased in juvenile hypertensive subjects. This study aimed to evaluate the vascular actions of Up 4A, typify the putative purinergic receptors that might mediate these effects and characterize the intracellular signaling pathways that may govern Up 4A responses. Up 4A induced a modest endothelium-dependent relaxation of rat aortic rings contracted with phenylephrine. From baseline, Up 4A induced concentration-dependent contractions that were significantly potentiated by endothelium removal or nitric oxide synthase inhibition. The contractile response induced by Up 4A was not tachyphylactic and was significantly reduced in the presence of P1 or P2X receptor antagonists, L-type Ca 2+ channel blocker and Rho-kinase inhibitor. Up 4A-induced contraction apparently involves superoxide anion formation since it was significantly reduced by treatment with apocynin or tempol. This study presents the unique findings that the endogenous compound Up 4A is able to induce relaxation in addition to contraction of rat aorta. Up 4A-induced contraction is modulated by nitric oxide production, mediated by P1 and P2X receptor activation, and involves L-type Ca 2+ channels, Rho-kinase pathway and superoxide formation.